2007
DOI: 10.1016/j.bbamem.2007.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of the lipid bilayer membrane made of calf lens lipids: EPR spin labeling studies

Abstract: The physical properties of a membrane derived from the total lipids of a calf lens were investigated using EPR spin labeling and were compared with the properties of membranes made of an equimolar 1-palmitoyl-2-oleoylphosphatidylcholine/cholesterol (POPC/Chol) mixture and of pure POPC. Conventional EPR spectra and saturation-recovery curves show that spin labels detect a single homogenous environment in all three membranes. Profiles of the order parameter, hydrophobicity, and oxygen transport parameter are pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
107
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(128 citation statements)
references
References 79 publications
18
107
2
Order By: Relevance
“…In parallel, membranes prepared from the lipids extracted from the different arteries of the three rat strains, hypertensive or not, were found to be structurally very similar. The fact that our data from reconstituted membranes differ from reports showing increased microviscosity of SHR membranes (2) in intact cell preparations shifts the focus to the role of cell membrane proteins or the protein-lipid rafts in the membrane microenvironment (33,34). Yet, a direct comparison of the reported ESR data (12) with our data is difficult since no ESR spectra are shown in the cited paper that refer only to the calculated parameters.…”
Section: Biological and Biophysical Membrane Properties And Vascular contrasting
confidence: 83%
“…In parallel, membranes prepared from the lipids extracted from the different arteries of the three rat strains, hypertensive or not, were found to be structurally very similar. The fact that our data from reconstituted membranes differ from reports showing increased microviscosity of SHR membranes (2) in intact cell preparations shifts the focus to the role of cell membrane proteins or the protein-lipid rafts in the membrane microenvironment (33,34). Yet, a direct comparison of the reported ESR data (12) with our data is difficult since no ESR spectra are shown in the cited paper that refer only to the calculated parameters.…”
Section: Biological and Biophysical Membrane Properties And Vascular contrasting
confidence: 83%
“…Electron spin resonance probe studies have shown that cholesterol contributes to the impermeability of oxygen across lens membranes ( 202,203 ). Maintaining low levels of oxygen is critical to the lens to prevent oxidation and opacifi cation.…”
Section: Cataract Lens Lipids Lifespan and Mortalitymentioning
confidence: 99%
“…The best monitor of these changes in the l o phase would be the profile of the oxygen transport parameter across the l o phase membranes. In membranes made of a binary mixture of phospholipids and cholesterol, these profiles changed from the bell shape at 30 mol% cholesterol, to the rectangular shape at 50 mol% cholesterol [22,50,51]. It is significant to note that the abrupt increase in the oxygen transport parameter, by a factor of 2-3, which is observed at 50 mol% cholesterol, occurs between the C9 and C10 position, which is approximately where the steroid ring structure of the cholesterol molecule reaches into the membrane.…”
Section: The Liquid-ordered Phase In a Liquid-disordered Or Solid-ordmentioning
confidence: 99%